1985
DOI: 10.1089/dna.1985.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Isolation of Human Cytochrome P-450 cDNAs Homologous to Dioxin-inducible Rabbit mRNAs Encoding P-450 4 and P-450 6

Abstract: Human cytochrome P-450s structurally related to 2,3,7,8-tetrachloro-p-dioxin (TCDD)-inducible rabbit P-450 4 and 6 have been cloned from a human liver cDNA library. The human P-450 4 cDNA clone, hpP-450 4, and the human P-450 6 cDNA clone, hpP-450 6, were identified by hybridization to rabbit P-450 4 and P-450 6 cDNAs, respectively. DNA sequence analysis demonstrates that hpP-450 4 is 83% and 75% homologous to rabbit P-450 4 and P-450 6 mRNAs, respectively, whereas hpP-450 6 is 79% and 72% homologous to rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Kimura et al, 1984;Okino et al, 1985;Quattrochi et al, 1985). Fish CYP1As share significant sequence similarity with both CYP1A1s and CYP1A2s (Morrison et al, 1995) and display a combination of catalytic functions characteristic of the mammalian isoforms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Kimura et al, 1984;Okino et al, 1985;Quattrochi et al, 1985). Fish CYP1As share significant sequence similarity with both CYP1A1s and CYP1A2s (Morrison et al, 1995) and display a combination of catalytic functions characteristic of the mammalian isoforms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that in humans, the gene equivalent to the major CL41Bz2-dioxin-inducible form in rabbit, P-450 4, and its counterparts in mice and rats, P3-450 and P-450d, respectively, does not exist (9). However, our laboratory has shown by DNA sequence analysis of a 600-base-pair (bp) cDNA clone called hpP-450 4, which was identified by hybridization of a rabbit P-450 4 cDNA clone (2) to a human cDNA library, that the human equivalent to rabbit P-450 4 gene is expressed in human liver (11). Southern blot analysis also showed that the P-450 4 and P-450 6 (P1-450) mRNAs were encoded by separate genes.…”
mentioning
confidence: 99%
“…However, Rainbow trout and salmonids are notable exceptions, this is consistent with the result of (Rabergh et al, 2000;Mahata et al, 2003). Mammalian, in contrast, generally possesses two paralogous CYP1A genes: CYP1A1 and CYP1A 2 (Kimura et al, 1984;Quattrochi et al 1985). Fish CYP1As share significant sequence similarity with both CYP1A1s and CYP1A2s (Morrison et al, 1995) and display a combination of catalytic function characteristic of the mammalian isoforms (Gorman et al, 1998).…”
Section: Induction Of Cyp1amentioning
confidence: 53%